Yersinia-induced uveitis in Ireland. Issue 12 (December 1988) - Larkin, D F; Cafferkey, M T; Eustace, P
Abstract : A prospective study was undertaken on 54 patients with an apparently idiopathic first attack of acute anterior uveitis. Blood samples were assayed for antibodies to Yersinia enterocolitica and Yersinia pseudotuberculosis, and tested for HLA type. Thirteen patients were found to have serological evidence of recent yersinia infection, eight with Y. enterocolitica and five with Y. pseudotuberculosis. The clinical course of uveitis did not differ from that typically found in HLA-B27 positive patients. Five patients were observed to develop non-ocular inflammation at a variable interval. The means by which eye inflammation follows yersinia infection is discussed in the light of recent theories on pathogenesis of HLA-B27 associated diseases.